Prevalence of HIV and hepatitis C markers among a cadaver population in Milan. Issue 4 (1st April 1999) - Cattaneo, C; Nuttall, P A; Molendini, L O; Pellegrinelli, M; Grandi, M; Sokol, R J
Abstract : AIMS: To examine the distribution of serological markers for HIV and hepatitis C virus (HCV) infection in a medicolegal population; to compare prevalence of HIV and HCV markers and cause of death; and to evaluate the risk of potential infection to personnel involved in medicolegal incidents and procedures. METHODS: Blood samples were collected at necropsy from 328 males and 69 females, aged 16 to 50 years at time of death, and tested for antibodies to HIV and HCV. The individuals were classified according to cause of death and whether there was known antemortem risk of infection. RESULTS: Overall, 134 subjects gave positive test results: 20 for anti-HIV, 69 for anti-HCV, and 45 for both. By cause of death, the total number of positives (and negatives) with the pairs of figures referring, respectively, to patients with and without known antemortem risks were: natural causes 3 (1), 8 (32); AIDS 2 (0), 0 (0); homicide 0 (2), 5 (24); suicide 3 (0), 9 (69); road traffic accidents 1 (0), 9 (81); other accidents 2 (3), 1 (12); drug overdose 74 (17), 7 (9); unknown causes 3 (2), 7 (11). CONCLUSIONS: The cases tested represented a predominantly young male population with a high prevalence of serological markers for HIV and HCV infection. The distribution of HIV and HCV positivity varied with the cause of death, probably reflecting the known association between high risk behaviour and infection. However, a substantial number of cases with no known risks also had markers for HIV and HCV, suggesting that there is a large unrecognised pool of potential infection in medicolegal practice.